FREQUENCY OF POSTOPERATIVE BACTERIURIA AND URINARY TRACT INFECTION IN PATIENT WITH DOUBLE J STENT (The Research of Medical Science Review, 2025)
Introduction and Objectives: Urinary tract infections and bacteriuria is considered as one of the major complications in patients undergoing surgical implants like catheters and stents such as Double J stents. This study was aimed to check the frequency of urinary tract infection among receptive patients of Double J stents in a hospital setting of Lahore. Material and Methodology: This cross-sectional study was conducted at Ihsan Mumtaz Hospital during August 2024-January 2025 on 96 patients indwelling Double J stent. A questionnaire was used for data collection which included questions related to basic patient demographics, reason for stenting, stenting based symptoms and risk factors contributing towards infection. Laboratory findings like urine culture were accessed to check the incidence of infection. Data obtained was entered categorically and analyzed using SPSS26. Results: Among 96 patients, 61(63.5%) were male while 35(36.5%) were female, while 26(27.08%) among them had diabetes. Majority of patients who got Double J stents presented with kidney stones 86(89.5%) followed by urethral stricture 10(10.4%). Among various clinical conditions following stenting, frequent urination 77(80%) was most commonly observed followed by fever 73(76%), discomfort 24(25%) and burning sensation 10(10.8%) during urination. Among these patients 65(67.7%) presented with bacteriuria and positive microbial growth on culture in comparison to pre-stenting samples with a significant value of 0.002 [p<0.005] indicating a strong correlation between the Double J stent and urinary tract infection. Conclusion: Double J stent can be potential source of urinary tract infection, removing it timely can be effective in preventing the infection.